To simplify, we can rewrite 27 as 3^3.
So the square root of 27 can be written as the square root of (3^3).
Taking the square root of each factor, we get:
√(3^3) = √(3*3*3) = 3√3
Therefore, 13 to the square root of 27 is equal to 13^(3√3).
Simplify 13 to the square root of 27
3 answers
how is that simplified?
Apologies for the misunderstanding.
To simplify 13 to the square root of 27, we need to calculate the actual value.
√27 = √(9 * 3) = √9 * √3 = 3√3
So, 13^(√27) = 13^(3√3).
To simplify 13 to the square root of 27, we need to calculate the actual value.
√27 = √(9 * 3) = √9 * √3 = 3√3
So, 13^(√27) = 13^(3√3).